THE INFLUENCE OF INFLUENCERS, PEERS AND EASE OF ACCESS TO ONLINE SHOPPING ON GEN Z CONSUMPTIVE BEHAVIOR AMONG STUDENTS OF THE FACULTY OF PSYCHOLOGY , STATE UNIVERSITY OF MAKASSAR - Muh. Homsur Homang Ropu; Supriadi Torro; Najamuddin Najamuddin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to: 1) analyze the influence of influencers on Gen Z consumptive behavior among students of the Faculty of Psychology , State University of Makassar, 2) analyze the influence of peers on Gen Z consumptive behavior among students of the Faculty of Psychology , State University of Makassar, 3) Analyze the influence of easy access to online shopping on Gen Z consumptive behavior among students of the Faculty of Psychology , State University of Makassar, This study uses a descriptive quantitative approach with a population of 2,064 students, the number of samples was determined using the Non Probabilty Sampling method with the slovin formula and a sample of 87 students was obtained, Data collection techniques were carried out through a questionnaire based on Google Forms and documentation. The validity test used a bivariate Pearson correlation and the reliability test was measured with Alpha Cronbach. Data analysis in the form of descriptive and inferential statistical methods with the help of the IBM SPSS Statistics for Windows application The results showed that: The results showed that: 1) Influencers, Peers, and Ease of Access to Online Shopping in Generation Z students of the Faculty of Psychology , State University of Makassar were respectively in the